Schedule of the 13th European Conference on Eye Movements 2005 - Marina Groner; Rudolf Groner; R. Müri; Kazuo Koga; Simon Raess; P P. (Bern Open Publishing, 2005)
This document contains the schedule of the 13th European Conference on Eye Movements, August 14-18 2005 in Bern, Switzerland